Undang-undang ITE sebagai Sarana Pencegahan Bisnis Curang Melalui Sarana eCommerce dalam Era Globalisasi - Hartono, Octavianus (Zenit, 2012)
Development in the field of information technology is very beneficialfor the growth of the economy of a country, but it also brings negative effects, such as online fraud. Moreover, consumers who do not take care of all their personal if this happens, the consumer’s property, either meterial or concept/ idea will be missing or damaged data and their personal accounts  can  be abused by responsible people. The development of information technology which  indeed gives a lot of positive effects for the world economy should be regulated in such a way so as not to cause negative effects for the parties using these facilities.  Keywords: globalization, economic development, business cheating